Immunohistochemical profiling of liver metastases and matched-pair analysis in patients with metastatic pancreatic ductal adenocarcinoma - Held, Thomas; Verbeke, Caroline S.; Strobel, Oliver; Rutkowski, Wiktor; Villard, Christina; Moro, Carlos Fernández; Del Chiaro, Marco; Büchler, Markus W.; Heuchel, Rainer; Löhr, J.-Matthias (Pancreatology, 2019)
Background - The purpose of the current study was to investigate the immunohistochemical (IHC) profile of liver metastases (LM) in patients with pancreatic ductal adenocarcinoma (PDAC). - Methods - Expression of 15 IHC markers in liver biopsies from 77 patients with PDAC, who were diagnosed between 2010 and 2014, were evaluated. In a separate subgroup analysis (n=12), paired samples (LM and primary tumor) from the same patient were investigated for IHC profile differences. - Results - LM samples were classified as pancreatobiliary-type (PB-type) in 72 patients (93.5%), intestinal-type (INT-type) in four patients (5.2%), and squamous in one patient (1.3%). There was no significant difference in overall survival (OS) between LM of the PB-type or INT-type (p=0.097). In a multivariate analysis, age <70 years (p=0.047), absence of SMAD4 mutation (p=0.026), absence of CDX2 expression (p=0.003), and well to moderate differentiation were significant prognostic factors for better OS in patients with LM (p=0.031). Analysis of paired tissue samples from LM and the primary tumor revealed a difference in CDX2 (50% increase, p=0.125) and SMAD4 (33% loss of SMAD4, p=0.375). - Conclusions - CDX2 expression and SMAD4 mutation indicate a poor outcome in patients with LM of PDAC. Matched-pair analysis revealed differences in distinct IHC marker expression.